Adsorption of nitrogen‐ and sulfur‐containing compounds on NiMoS for hydrotreating reactions: A DFT and vdW‐corrected study. Issue 12 (17th September 2015) - Rangarajan, Srinivas; Mavrikakis, Manos
Abstract : Adsorption of 35 molecules, comprising of organonitrogen and organosulfur compounds and hydrocarbons relevant to hydrotreating, was studied on the nickel‐promoted metal edge of molybdenum sulfide catalysts using periodic DFT, accounting for van der Waals interactions in several cases. Basic molecules tend to adsorb via their nitrogen atoms directly on top of nickel atoms while nonbasic molecules adsorb via carbon atoms relatively weakly. Molecular size, electron density, and alkyl substitution affects binding at the GGA‐PW91 level of theory. van der Waals corrections influence adsorption geometry and lead to significant additional stabilization of adsorbates. The differential binding energy of nitrogen‐containing compounds decreases by 0.2–0.3 eV for each additional molecule added on the edge and their presence destabilizes the binding of organosulfur compounds by more than 0.2 eV. The inhibition of hydrodesulfurization is suggested to arise from site blocking and destabilization of reaction intermediates and transition states by organonitrogen compounds. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4036–4050, 2015